2021
DOI: 10.1007/s10552-021-01462-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in colorectal cancer knowledge and screening intention among Ohio African American and Appalachian participants: The screen to save initiative

Abstract: African Americans and Appalachians experience greater incidence and mortality rates of colorectal cancer due to factors, such as reduced prevalence of screening. An educational session (the Screen to Save Initiative) was conducted to increase intent to screen for colorectal cancer among African Americans and Appalachians in Ohio. Using a community-based approach, from April to September 2017, 85 eligible participants were recruited in Franklin County and Appalachia Ohio. Participants completed a knowledge asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 53 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…Colorectal cancer is the second most common cause of cancer mortality in the United States [ 9 ]. However, its mortality risk and cure rate are getting progressively better due to the early detection, and thus early cure is possible [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer is the second most common cause of cancer mortality in the United States [ 9 ]. However, its mortality risk and cure rate are getting progressively better due to the early detection, and thus early cure is possible [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social media and TV channels, as well as screen-based educational interventions, such as that given by PowerPoint, are effective approaches to address the problem [43,44]. Indeed, a study conducted in UAE has revealed that social media was the primary source of information about cancer in 66% of the participants [26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is crucial to improve people's knowledge and awareness of CRC screening to promote the conversion of knowledge to practice (i.e., to the attendance of screenings). Education interventions provided by PowerPoint could be an effective way to facilitate the improve of knowledge and awareness (25,26).…”
Section: Discussionmentioning
confidence: 99%